If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 4)(x) = 20 Reorder the terms: (4 + 2x)(x) = 20 Reorder the terms for easier multiplication: x(4 + 2x) = 20 (4 * x + 2x * x) = 20 (4x + 2x2) = 20 Solving 4x + 2x2 = 20 Solving for variable 'x'. Reorder the terms: -20 + 4x + 2x2 = 20 + -20 Combine like terms: 20 + -20 = 0 -20 + 4x + 2x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-10 + 2x + x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-10 + 2x + x2)' equal to zero and attempt to solve: Simplifying -10 + 2x + x2 = 0 Solving -10 + 2x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '10' to each side of the equation. -10 + 2x + 10 + x2 = 0 + 10 Reorder the terms: -10 + 10 + 2x + x2 = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 2x + x2 = 0 + 10 2x + x2 = 0 + 10 Combine like terms: 0 + 10 = 10 2x + x2 = 10 The x term is 2x. Take half its coefficient (1). Square it (1) and add it to both sides. Add '1' to each side of the equation. 2x + 1 + x2 = 10 + 1 Reorder the terms: 1 + 2x + x2 = 10 + 1 Combine like terms: 10 + 1 = 11 1 + 2x + x2 = 11 Factor a perfect square on the left side: (x + 1)(x + 1) = 11 Calculate the square root of the right side: 3.31662479 Break this problem into two subproblems by setting (x + 1) equal to 3.31662479 and -3.31662479.Subproblem 1
x + 1 = 3.31662479 Simplifying x + 1 = 3.31662479 Reorder the terms: 1 + x = 3.31662479 Solving 1 + x = 3.31662479 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 3.31662479 + -1 Combine like terms: 1 + -1 = 0 0 + x = 3.31662479 + -1 x = 3.31662479 + -1 Combine like terms: 3.31662479 + -1 = 2.31662479 x = 2.31662479 Simplifying x = 2.31662479Subproblem 2
x + 1 = -3.31662479 Simplifying x + 1 = -3.31662479 Reorder the terms: 1 + x = -3.31662479 Solving 1 + x = -3.31662479 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = -3.31662479 + -1 Combine like terms: 1 + -1 = 0 0 + x = -3.31662479 + -1 x = -3.31662479 + -1 Combine like terms: -3.31662479 + -1 = -4.31662479 x = -4.31662479 Simplifying x = -4.31662479Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.31662479, -4.31662479}Solution
x = {2.31662479, -4.31662479}
| X+0.3=-0.4 | | -6.75=x+5.4 | | 4(2x+4)=10x+15-2x+17 | | 265=-5x | | 14=k+9 | | 5-6w=-13 | | 9x-2+55=13+14x | | -4x-36=-72 | | -16+m=-20 | | 5=9+4x | | 0.5(4x+8)(x)=20 | | 4c=16.8 | | -19=x-17 | | 6y-(2y-5y)=29 | | 1.48(k+3)=5.92 | | b+14=1 | | d+(-7)=12 | | 6x+3=98-3x+6 | | 7+1-6x+3x=3x-5x | | q+6.44=0.72 | | k+18=32 | | -p+7=13 | | 5(-2v+6)-4v=-2(v-3) | | 7.2=1.8x | | -2*-0.36=x | | -20=a-8 | | 7.1=x-1.4 | | -2.65(g-10)=-15.9 | | 2a^2-6a+13=0 | | v-19=-36 | | 17.6=3.9(p+3)+2 | | -8h=-48 |